PENGGUNAAN SUBSTRAT WHEY TAHU UNTUK PRODUKSI BIOMASSA OLEH PEDIOCOCCUS PENTOSACEUS E.1222 - Yeni, Anja Meryandini, dan Titi Candra Sunarti (Jurnal Teknologi Industri Pertanian, 2016)
Lactic acid bacteria (LAB) has been widely used as a starter culture. The most important factor fordeveloping industrial starter culture is the selection of a good and cheap medium. Tofu whey (TW) is the liquidwaste of the tofu production which potentially be able to use as a growth medium for LAB. On this research, TWwas fermented by Pediococcus pentosaceus E.1222 for 24 hour, at 37°C, pH 6, and without agitation. This workwas conducted in several stages, first stage was selection of carbon source and the result showed that TWsupplemented glucose gives the highest LAB number was 4.5×108 CFU/mL and spesific growth rate (μmax) 0.65h-1. The next stage was determining glucose concentration and the highest growth was TW supplemented 5%glucose, where the number of LAB reached 1.4×1010 CFU/mL and μmax 0.91 h-1. The next stage was scaling upthe starter production, fermentations were initially performed at scale 150 mL medium, then medium was scaledup to 500 mL and 1 L. The result showed a slight decreasing in number of LAB on each volume, from 1.1×1010CFU/mL (150 mL), 1.09×1010 CFU/mL (500 mL), and 1.03×1010 CFU/mL (1L); and declining of μmax is found tobe 0.91–0.90 h-1.Keyword: Lactic acid bacteria, starter culture, tofu whey, Pediococcus pentosaceus